Educating children with disabilities: Comparative evidence from Ethiopia, Burkina Faso and Niger - Privilege Hang'andu; Emmanuel Kodwo Mensah; Elena Nikolova; Elizabeth Hayward (Global Labor Organization (GLO), 2023)
Education is a fundamental human right and it is a global Sustainable Development Goal to “ensure inclusive and equitable quality education for all.” Many children with disabilities in low-income countries, however, continue to be excluded from educational opportunities at great cost to themselves, their families, and the communities in which they live. Realizing the right to inclusive education for children with disabilities requires policies and practices that are tailored to and effective for unique regional and local contexts. Using new qualitative data collected in 2020 (based on a desk review and key informant interviews), this chapter explores the inclusiveness, equality, and quality of education for children with disabilities in three African countries: Ethiopia, Burkina Faso, and Niger. The study countries are at the bottom of the Human Development Index ranking of 189 countries worldwide (Ethiopia 173, Burkina Faso 182, Niger 189, data from 2020). Despite state commitments to education as a human right and legislative support for inclusive education in each country, social, economic, political, and financial factors at the family, community, and system levels contribute to the continued marginalization of children with disabilities. The insights from this multi-country analysis highlight the importance of locally informed and context-specific approaches but also point to broader lessons for the study and promotion of inclusive education in low-resource settings. These insights provide a starting point for further investigation of disabilityinclusive education on the African continent and in the developing world.
Keywords: I21; I25; I28; 330; disability; inclusive education; exclusion; children with disabilities; school; developing countries